2017
DOI: 10.5606/archrheumatol.2017.6216
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Tryptophan/Kynurenine Pathway Relevance With Immune System Biomarkers of Low Energy Trauma Hip Fractures in Osteoporotic Patients

Abstract: Objectives: This study aims to evaluate tryptophan degradation and clarify whether altered levels of kynurenine and tryptophan (Kyn/Trp) ratio could be correlated to osteoporotic hip fractures via immune system. Patients and methods:The study included 60 patients with osteoporotic hip fracture (20 males, 40 females, mean age 76.6±6.9 years; range 59 to 95 years). Patients were divided into two as patients with collum femoris fractures (group 1; n=23) and intertrochanteric fractures (group 2; n=37). Fifteen hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Some role of inflammation would certainly be suggested by the association between increased levels of kynurenine or its catabolites and the progress and degree of bone dysfunction, since the first enzyme of the kynurenine pathway, IDO, is induced and activated by several inflammatory stimuli such as interferon-γ, LPS and TNFα. This activation of the kynurenine pathway has been demonstrated in human mesenchymal stem cells with a strong positive correlation between kynurenine pathway activity and osteoblast formation 57,59 . Correspondingly, inhibition of the kynurenine pathway using an inhibitor of IDO produced a reduction of osteoblastogenesis and genetic deletion of IDO resulted in the loss of bone structure and strength with fewer osteoblasts and a higher proportion of osteoclasts than wild-type animals.…”
Section: Kynurenine Metabolism and Shla-gmentioning
confidence: 68%
“…Some role of inflammation would certainly be suggested by the association between increased levels of kynurenine or its catabolites and the progress and degree of bone dysfunction, since the first enzyme of the kynurenine pathway, IDO, is induced and activated by several inflammatory stimuli such as interferon-γ, LPS and TNFα. This activation of the kynurenine pathway has been demonstrated in human mesenchymal stem cells with a strong positive correlation between kynurenine pathway activity and osteoblast formation 57,59 . Correspondingly, inhibition of the kynurenine pathway using an inhibitor of IDO produced a reduction of osteoblastogenesis and genetic deletion of IDO resulted in the loss of bone structure and strength with fewer osteoblasts and a higher proportion of osteoclasts than wild-type animals.…”
Section: Kynurenine Metabolism and Shla-gmentioning
confidence: 68%
“…However, neither kynurenine nor KYNA content was altered [56]. Similarly, Dinçel et al [59] observed reduced tryptophan content and unaltered levels of kynurenine in the plasma of humans with osteoporotic hip fractures. Furthermore, reduced levels of erythrocyte tryptophan were found in male idiopathic osteoporotic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Linolenate, a precursor of arachidonate (an inflammatory mediator), was found to be increased, much like corticosterone and cortisol, which are inhibitors in the proinflammatory pathway [ 67 ]. Kynurenine, a metabolite of tryptophan, was elevated in the post-reaming plasma, while tryptophan itself declined, pointing towards an upregulated activity of the kynurenine pathway [ 68 , 69 ]. It should be pointed out that the increase in the kynurenine/tryptophan ratio has been considered a marker for indoleamine 2,3-dioxygenase (IDO) activity [ 69 ].…”
Section: Metabolomics In Research Of Bone Diseasesmentioning
confidence: 99%